THRUST ANALYSIS ON 250 WATTS DC ELECTRIC MOTOR FOR LOCOMOTION BOAT - Samosir, Rahmad; Sebayang, Melya Dyanasari; Pane, Medyawanti; Silaban, Alberto Haryanto (International Journal of Research -GRANTHAALAYAH, 2021)
To make it easier for farmers in terms of maintenance and transportation of community-owned coconut and palm oil crops, the team tried to make a design for testing the thrust of a 250 Watt DC motor powered by solar heat for boat propulsion, by testing the boat propeller with variations in the diameter of the propeller 17.5 mm, 15 mm, 15.5 mm, 14.8 mm, and 14.5 mm, as well as testing with variations in driving rotation and variations in driving rotation with the number of gear teeth 11, 16, 20, and 22. From the calculation of the torque obtained is 1,090 Nmm so that the diameter is obtained propeller is 5 mm. Thrust force test results obtained vary depending on the diameter and variations of the rotation of the propeller drive so that an adequate diameter is obtained by using a diameter of 14.8 mm with a current of 9.2 A with a thrust of 7.5 kgf. Meanwhile, for an adequate variety of the driving speed, the number of teeth is 20 and the thrust is 7.5 kgf and the current is 10. This value meets the requirements because the current strength does not exceed 10 A. From the test results, it can be concluded that the design and analysis are very fulfilling needs.